2019
DOI: 10.1002/erv.2713
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional brain correlates of altered taste processing in anorexia nervosa: A systematic review

Abstract: Objective: A growing body of empirical literature indicates altered taste perception in individuals with anorexia nervosa (AN). However, it remains unknown whether the observed impairments in the neural processing of taste stimuli represent etiopathogenetic factors of AN or whether they are a secondary consequence of malnutrition.Method: In the current systematic review, scientific studies were identified using the MEDLINE, PsycINFO, and Scopus databases. A supplemental search was performed by searches through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Specifically, ventromedial prefrontal cortex connects valuation of an event (its reward) with its relevance to an individual, a process proposed to underlie the establishment of a stable identity (D'Argembeau, 2013). Critically, differences in both behavioural and neural responses to rewards have been observed in AN, including both food rewards (Kot et al, 2019) and social rewards (McAdams et al, 2015). Activation of subcortical reward regions in conjunction with midline cortical structures has been proposed to mediate the development of social identity during adolescence (Pfeifer & Berkman, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, ventromedial prefrontal cortex connects valuation of an event (its reward) with its relevance to an individual, a process proposed to underlie the establishment of a stable identity (D'Argembeau, 2013). Critically, differences in both behavioural and neural responses to rewards have been observed in AN, including both food rewards (Kot et al, 2019) and social rewards (McAdams et al, 2015). Activation of subcortical reward regions in conjunction with midline cortical structures has been proposed to mediate the development of social identity during adolescence (Pfeifer & Berkman, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The results of studies using functional magnetic resonance imaging (fMRI) indicate that brain reward circuits are more responsive to food stimuli in AN and that the brains of individuals who have recovered from AN are characterized by aberrant neural responses to pleasant and aversive taste stimuli [ 24 , 25 , 26 , 27 ] examined women who had recovered from AN and showed that the disturbances of gustatory processing in the central nervous system do not necessarily coexist with aberrations in subjective taste sensations.…”
Section: Discussionmentioning
confidence: 99%
“…As bulimia nervosa patients may have a deficit in satiation (Keel et al, 2018 ), we speculate that neuroimaging studies could aid in further understanding of disease mechanisms, through assessment of activation in the brainstem and midbrain in patients and controls in response to experimental gastric distention. Furthermore, in patients with anorexia nervosa, who may have altered taste processing (Kot, Kucharska, Monteleone, & Monteleone, 2020 ), neuroimaging studies could aid in elucidating the role of hypothalamic and insular activation in response to taste.…”
Section: Discussionmentioning
confidence: 99%